Research on the Influence of the Overseas Background of the Executive Management Team on the Internationalization Performance of Chinese Enterprises - Xu, Guoliang; Jiang, Ting (International Journal of Innovative Research and Scientific Studies, 2025)
In the context of globalization, enterprise internationalization is crucial for growth and competitiveness, and the executive team significantly impacts a company’s strategic choices and performance. This paper focuses on analyzing the influence of the overseas background of the senior management team on the internationalization performance of Chinese enterprises. By reviewing relevant literature and theories, including agency theory, upper echelons theory, and technological innovation theory, it explores the underlying mechanisms. Using data from China’s A-share listed companies from 2008 to 2022, a regression equation is constructed for empirical analysis. The findings indicate that the overseas background of the management team promotes enterprise internationalization performance. Mechanistically, executives with overseas backgrounds enhance internationalization performance by increasing the degree of diversification strategy and R&D investment. In terms of enterprise scale, large-scale enterprises can better utilize the innovation and decision-making capabilities of overseas-background executives for strategic actions like exports, overseas mergers and acquisitions, and overseas factory establishment, thus improving international performance. Regarding property rights, in private enterprises, overseas-background executives can freely express opinions and address internationalization issues, reducing obstacles and enhancing performance. This research provides theoretical and practical guidance for Chinese enterprises in their internationalization efforts.